Pengaruh Karakteristik Internal dan Eksternal Petani Terhadap Keberhasilan Usaha Bibit Sengon (Paraserienthes falcataria) (Suatu Kasus di Kebun Bibit, Jawa Barat) - Acad Sudrajat; Dety Sukmawati; Euis Dasipah (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2022)
Sengon plants are dominant in their development, especially in community forest management. The availability of a market that accommodates community forest products makes farmers active in planting commercial tree species even on narrow lands using agroforestry methods so that they get profits. This research uses a qualitative research type. The research was conducted in Cicalengka District, Bandung Regency with the unit (subject) of analysis is the Giri Jaya Farmers Group and the object of the research is the internal and external characteristics of producing sengon. Variable X1, namely the internal characteristics of farmers is something inherent in the farmers, such as age, education, farming experience and number of dependents in the family. These internal characteristics will affect the expertise of farmers in sengon cultivation. Variable X2, namely External Characteristics is a characteristic that is influenced by external influences such as information media, interaction with other farmers, assistance and counseling. Variable Y, namely the Success of Sengon Seeds Business. The success of sengon production is seen from the quantity and quality. Measurement of variables with ordinal measuring scale, assessed with 3 scores. with a population size of 60 people. The sampling technique was using the saturated sample (census) method. The analysis technique used multiple linear regression analysis with hypothesis testing using the SPSS computer program. The internal characteristics of farmers have a significant effect on the success of the sengon seedling business (0.175). Internal characteristics that have an effect on increasing the production of sengon seedlings are the age and experience of the farmers. The external characteristics of farmers significantly influence the success of the sengon seedling business (0.124). External characteristics that have an effect on increasing the production of sengon seeds are the activities of mentoring and counseling farmer